O consumo e o discurso publicitário intercultural : as lógicas produtivas da propaganda internacional de Havaianas - Mündel, Jane de Freitas Misseno (2017)
The process of internationalization of the market, of social contact and of communications the current ambience new cultural relations and dialogues capable of producing profound changes in society and consumption. Having as main object the discourse intercultural publicity, this study had as objective to understand the strategic narratives that make possible the relation of production and consumption in multicultural settings. And also, identify as the discourse - which includes representations, identities, imaginary - makes sense in different cultural contexts. For this, we deal with crucial concepts such as Globalization and Globalization, Culture of Consumption, Intercultural Communication, Advertising and Production of Narratives, Identity and Imaginary. Supported in Line Speech Analysis French and in the theoretical frameworks essential for the interpretation of our empirical object - campaigns of the Havaianas sandals - we enter the history, the the company's universe to then investigate how a communication produced in the Brazil, aiming at the consumption of a Brazilian brand and product abroad, makes sense in intercultural environments. The result led us to the construction of a summary production logics analyzed and contributed to our corpus: 6 international Havaianas, printed in the print media from 2007 to 2013. Our research on the production of Havaianas intercultural discourse has given rise to the perception that, despite creativity, the brand maintains a strategic production of their international narratives, with an exaltation of the identity and Brazilian lifestyle.